Diversitas Tumbuhan Paku (Pteridophyta) di KHDTK Gunung Bromo UNS, Karanganyar, Jawa Tengah - Fisani, Musfinda Al; Nurmiyati, Nurmiyati (Universitas Sebelas Maret, 2022)
The fern diversity research at KHDTK Gunung Bromo was conducted in March-July 2022. KHDTK Gunung Bromo is a forest area that has potential for biodiversity. One of the existing diversity is the type of fern (Pteridophyta). Determination of the research location was carried out using the Pusposive Sampling technique, where the research plot was placed in the most favorable conditions in a protected forest area. The purpose of this study was to determine the level of diversity of Preridophyta in KHDTK Gunung Bromo. Data collection was carried out exploratory and using a 5x5 m square plot method as many as 15 pieces placed at the observation location. The results obtained 13 species of Pteridophyta grouped into 5 families, namely Thelypteridaceae, Polypodiaceae, Dryopteridaceae, Lygodiaceae, and Pteridaceae. Species found include: Thelypteris palustris, Sphaerostephanos unitus, Phegopteris connectilis, Christella dentata, Polypodium vulgare, Pyrrosia longifolia, Pleocnemia irregularis, Lygodium flexuosum, Lygodium japonicum, Lygodium circinnatum, Pteris ensiformis, Adiantum cuneatum, and Pteris tripartita. The highest Important Value Index (INP) was found in the species Pteris ensiformis at 61.210% with a total of 344 individuals. The Shannon-Wienner Diversity Index (H') showed a moderate category of 1.978 and a uniformity index of 0.771 including a high category. The dominance index (C) is low with a value of 0.188. The diversity of Pteridophyta at the study site is supported by environmental conditions that tend to be shaded by large trees and high plants so that the air humidity is high.